Intention of Social Media Adoption among Undergraduate Students of Business Schools in Kathmandu Valley (Journal of Business and Management Research, 2022)
This paper investigated the intention of social media adoption among undergraduate students in business schools during 2020. A purposive sampling technique was used to collect data from 200 undergraduate students in the Kathmandu Valley using self-administered questionnaires. Data were analyzed by applying Partial Least Squares-Structural Equation Modeling (PLS-SEM). This research paper found a significant positive influence of resource sharing on behavior intention of social media adoption. The hypothesis showed that perceived ease of use partially mediated the relationship between collaboration and behavior of educational use of social media. However, the research found no significant influence of perceived ease of use, and perceived usefulness on behavior intention of social media adoption. Using the findings of this paper, the research paper discussed the theoretical and practical implications for researchers and educators. The paper incorporates resource sharing and collaboration variables to the existing TAM framework.